2009
DOI: 10.1186/1471-2393-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrinolytic agents in post partum haemorrhage: a systematic review

Abstract: Background: Post partum haemorrhage is a leading cause of maternal death worldwide. It also contributes to maternal morbidity as women may require a hysterectomy to control bleeding, or may require a blood transfusion, which can transmit viral infections. Anti-fibrinolytic agents have been proposed as a treatment for post partum haemorrhage. We conducted a systematic review to assess the effectiveness and safety of anti-fibrinolytic agents in post partum bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 14 publications
2
78
0
9
Order By: Relevance
“…A recent meta-analysis on TXA in pregnancy and postpartum [118] by Peisidis et al [118] included several quasi-blinded trials [119−121] excluded from the above Cochrane review, and found a combined estimated decrease of blood loss by 32.5 mL in TXA pre-caesarean section vs a control. A similar effect of TXA was found in a separate meta-analysis by Ferrer et al [122] in a reduction of postpartum blood loss by 92 mL compared with the control.…”
Section: Obstetric and Gynecologysupporting
confidence: 60%
“…A recent meta-analysis on TXA in pregnancy and postpartum [118] by Peisidis et al [118] included several quasi-blinded trials [119−121] excluded from the above Cochrane review, and found a combined estimated decrease of blood loss by 32.5 mL in TXA pre-caesarean section vs a control. A similar effect of TXA was found in a separate meta-analysis by Ferrer et al [122] in a reduction of postpartum blood loss by 92 mL compared with the control.…”
Section: Obstetric and Gynecologysupporting
confidence: 60%
“…53 Although evidence suggests that this drug reduces postpartum bleeding, the quality of the existing trials is poor and none have been large enough to assess the effect of TXA on end points that are important to women. 54 A large trial is currently under way to assess the effect of TXA on the risk of death and hysterectomy in women with postpartum haemorrhage.…”
Section: Future Clinical Researchmentioning
confidence: 99%
“…Sekhavat, et al [22] in their study used TXA immediately before CS in pregnant women and showed that bleeding was reduced until two hours after CS and the Hb levels at 24 hours after surgery were higher than control group [22]. Ferrer, et al [23] in their systematic review of using TXA to control PPH concluded TXA may reduce bleeding after delivery, but further studies are needed to prove this effect [23]. The present study as the above studies achieved to the positive results about the effects of TXA to decrease PPH and puerperal bleeding.…”
Section: Discussionmentioning
confidence: 99%